Analysis Of Online Arabic Language Proficiency Test Questions Based On Bloom's Cognitive Taxonomy - Mahmudi, Ihwan; Bujanah, Hanifa; Ismail, Moh.; Saifulloh, Ahmad; Fatawi, Izzul; Hasanah, Maghfirotul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
One of the visions of the University of Darussalam Gontor is to become a center for the language of the Qur'an. An online Arabic language test is conducted to measure its students' Arabic proficiency. This study aims to analyze the difficulty level of the online Arabic language test at the University of Darussalam Gontor based on Bloom's Cognitive Taxonomy. The research employs a descriptive quantitative method. The data was collected from students' test scores, which cover three language skills: reading (qira'ah), listening (istima'), and writing (kitabah). The sample was randomly selected, comprising 135 students for the writing test, 127 for the listening test, and 129 for the reading test. The results indicate that the difficulty level of the questions based on students' test results for the reading skill shows that 10% of the questions were classified as difficult, 42% as middle, and 48% as easy. For the listening skill, 17% of the questions were classified as difficult, 44% as middle, and 39% as easy. There were no difficult questions in the writing skill, with 83% being middle and 17% easy. Regarding the cognitive domains of Bloom's taxonomy, 21% of the questions in reading test (qiraah) were categorized as HOTS, 52% as MOTS, and 17% as LOTS. For the listening test (istima), 11% of the questions were classified as HOTS, 67% as MOTS, and 11% as LOTS, while for the writing test, 10% were categorized as HOTS, 55% as MOTS, and 25% as LOTS.